ANALISIS KERAWANAN LONGSOR LAHAN DI KECAMATAN NGARGOYOSO KABUPATEN KARANGANYAR TAHUN 2023 - Muhammad Annas; Chatarina Muryani; Setya Nugraha (INDONESIAN JOURNAL OF ENVIRONMENT AND DISASTER, 2023)
Karanganyar Regency is one of the districts in Central Java that has natural disasters in the form of landslides caused by varying slopes, with Ngargoyoso District having a high level of landslide vulnerability. This research aims to determine the vulnerability to landslides in Ngargoyoso District. The method involves analyzing land units using scoring and weighting of six key parameters: slope, rock structure, soil type, fault location, rainfall, and land vegetation cover, which are then arranged as an overlay. The research results identified 94 land units divided into two classes of vulnerability to landslides: medium class and high class. The medium vulnerability class covers an area of ​​3,063.90 hectares or around 49.63% of the total area of ​​Ngargoyoso District. In comparison, the high vulnerability class has an area of ​​3,063.90 hectares, or around 50.37% of the total area of ​​the subdistrict. These results provide a clear picture of the vulnerability to landslides in the region, which can be used as a basis for disaster mitigation planning and better land management.